2020
DOI: 10.1007/s00420-020-01575-w
|View full text |Cite
|
Sign up to set email alerts
|

Killing two birds with one stone: how intervening when witnessing bullying at the workplace may help both target and the acting observer

Abstract: Objective This study examines under which conditions being an observer of bullying can be detrimental to health and well-being. It was hypothesized that health-related problems following observations of bullying are determined by (1) whether the observer has been exposed to bullying her/himself and (2) whether the observer have tried to intervene in the bullying situation that they witnessed. Methods The study was based on a longitudinal probability survey of the Swedish workforce, with an 18-month time lag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
(100 reference statements)
2
11
0
2
Order By: Relevance
“…The present study also gives an additional insight into a previous study based on the same sample that showed that not intervening when witnessing bullying was associated with later mental health problems (Nielsen et al, 2021). Mental health problems are known consequences of exposure to bullying behaviors (Nielsen & Einarsen, 2012).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The present study also gives an additional insight into a previous study based on the same sample that showed that not intervening when witnessing bullying was associated with later mental health problems (Nielsen et al, 2021). Mental health problems are known consequences of exposure to bullying behaviors (Nielsen & Einarsen, 2012).…”
Section: Discussionsupporting
confidence: 58%
“…Based on a longitudinal probability survey of the Swedish working population, we investigated the risks associated with the actions that follow witnessing bullying at one's workplace-the risks if intervening, and the risks if remaining inactive. As bullying is an extreme stressor and a form of psychological violence at work, intervening in an ongoing bullying situation is potentially beneficial for the health and well-being of the victim (Nielsen et al, 2021). However, intervening may also increase the risk of becoming the next target, so hesitation and unwillingness to act may be understandable (Bjørkelo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Role clarity and order in the organization was measured using a scale from the Psychosocial Work Environment Questionnaire (PSYWEQ, Rosander and Blomberg, 2018 ) called ‘Roles in the organization’ (RIM, Rosander and Blomberg, 2019 ; Nielsen et al , 2021 ). It contains six items that focus on: (i) unclear roles, responsibilities, and tasks; (ii) a clear division of tasks; (iii) clear roles; (iv) an orderly organization; (v) well-functioning routines and organization; and (vi) clear role expectations.…”
Section: Methodsmentioning
confidence: 99%